Smoking and obesity in Chile's Third National Health Survey: light and shade - Vivienne C. Bachelet; Fernando Lanas (Pan American Health Organization, 2018)
The Chilean Ministry of Health recently disclosed the first results of the 2016-2017 National Health Survey (Encuesta Nacional de Salud, ENS). The survey was cross-sectional and used a multistage stratified random sampling strategy resulting in a final sample of 6 233 persons ≥ 15 years old, with national, regional, and urban/rural representativeness. The survey results show consistent reductions in tobacco consumption compared to previous national health surveys (ENS 2003 and ENS 2009-2010), most likely due to stringent tobacco control policies enacted in the last 10 years. However, the results also show that there were alarming increases in obesity in the last 15 years. Stronger regulatory policies may be needed to curb the obesity epidemic that besets Chile, along the lines of what was done with tobacco use. The lesson learned seems to be that pushing for stronger policy measures leads to good results, as seems to be the case for tobacco use, while weak measures may not be sufficient for the scale of the health epidemics Chile is now facing, such as excess weight.